Tests of the fund accounting model for local governments* - INGRAM, ROBERT W. (Contemporary Accounting Research, 1986)
Abstract. This study examines the association between an index of compliance with the fund model and bond risk measures. Several additional factors were posited to be associated with bond risk and to be correlated with the fund index. These variables were included in the analysis to control for possible spurious results. The results were consistent with the hypothesis that the fund accounting model provides information associated with creditor decisions. The fund index was negatively correlated with systematic and total bond risk after controlling for other factors. The index contributed marginally in explaining the variation in measures of risk for a sample of 214 cities. The results were insensitive to several alternative models that were examined but that are not reported in detail in the study. Résumé. Cette étude porte sur le lien entre un indice de conformité au modèle de comptabilité par fonds et les mesures de risque obligataire. Plusieurs facteurs étaient supposés être reliés au risque obligataire et correlés avec l'indice de fonds. Ces variables ont été incorporées à l'analyse afin de contrôler la possibilité de résultats trompeurs. Les résultats ont révélé une cohérence avec l'hypothèse voulant que le modèle de comptabilité par fonds fournisse de l'information reliée aux décisions des créanciers. L'indice de fonds était correlé négativement au risque obligataire, systématique et total, en contrôlant l'effet des autres variables. L'indice n'a pu expliquer*** la variation des mesures de risque pour un échantillon de deux cents quatorze municipalités. Les résultats n'ont pas été affectés par l'utilisation de diverses variantes de modèles qui, sans avoir été l'objet d'un compte rendu détaillé, furent examinés dans le cadre de cette étude.